A new combination in the genus Liparis (Orchidaceae) for the Italian flora - Bartolucci, Fabrizio; Galasso, Gabriele (Phytotaxa, 2016)
The genus Liparis Richard (1817: 21) comprises about 320 species, broadly distributed worldwide but mainly in tropical and subtropical areas (Pridgeon et al. 2005). In Europe only the circumboreal L. loeselii (Linnaeus 1753: 947) Richard (1817: 38) occurs (Hultén & Fries 1986). Recently the new taxon L. loeselii (L.) Rich. subsp. nemoralis Perazza et al. (2012: 489) was described from northeastern Italy. It is endemic to Friuli Venezia Giulia, Veneto and Trentino-Alto Adige (Perazza & Lorenz 2013, Peruzzi et al. 2014).